A Sustainable Eco-Friendly One-Pot Multicomponent Synthesis via Mechanochemical Reaction Using Lemon Juice - Khalaf, Mohamed, Shaema; Alazzawi, Shaymaa K. (International Journal of Aquatic Research and Environmental Studies, 2026)
Green and sustainable chemistry have become very important in modern organic synthesis, especially in reactions that use solvent-free conditions, multicomponent reactions, grinding techniques, and natural catalysts and also in order to grant all chemical reactions the status of safe and eco-friendly reactions. In this research, according to the above point of view the sulfathiazole diazonium salt (1) was prepared and react with malononitrile in the presence of sodium acetate to yield aryl hydrazone propane dinitrile (2), which was then reacted with hydrazine in acidic media to obtain the building unit 2,5-diamino pyrazole (3). Subsequently, we used the one-pot threecomponent reactions among compound (3), aromatic aldehydes and malononitrile, using lemon juice as acid through free-solvent grinding technique. The 2-amino pyridine carbonitrile derivatives (4-7) were obtained in good yield using water as recrystallizing agent. Actually these compounds were illustrated via FT-IR and 1H-NMR spectroscopy and also by theoretical biological study using the Molecular Docking program.